Optically Induced Picosecond Lattice Compression in the Dielectric Component of a Strongly Coupled Ferroelectric/Dielectric Superlattice (Adv. Electron. Mater. 6/2022). (12th June 2022) - Sri Gyan, Deepankar; Lee, Hyeon Jun; Ahn, Youngjun; Carson, River B.; Carnis, Jerome; Kim, Tae Yeon; Unithrattil, Sanjith; Lee, Jun Young; Chun, Sae Hwan; Kim, Sunam; Eom, Intae; Kim, Minseok; et al.
Abstract : Ultrafast Optical Excitation The structure of an epitaxial BaTiO3 /CaTiO3 ferroelectric/dielectric superlattice responds to aboveband gap ultrafast optical excitation with a compression of the dielectric CaTiO3 layer is presented in article number 2101051 by Paul G. Evans and co‐workers. This unusual response is a consequence of the screening of the polarizing field due to the ferroelectric BaTiO3 layer. The distortion is developed on the picosecond timescale and is apparent in ultrafast x‐ray free‐electron laser diffraction measurements.